A bendable nickel oxide interfacial layer via polydopamine crosslinking for flexible perovskite solar cells. Issue 25 (11th March 2019) - Duan, Xiaopeng; Huang, Zengqi; Liu, Cong; Yang, Jia; Tan, Licheng; Chen, Yiwang
Abstract : Flexible perovskite solar cells based on polydopamine cross-linked NiO x exhibited over 70% efficiency retention after 1000 bending cycles. Abstract : Bendable nickel oxide (NiO x ) was first fabricated via polydopamine (PDA) modification and applied as an interfacial layer in flexible perovskite solar cells. PDA cross-linked NiO x could release mechanical stress to eliminate the inherent brittleness of inorganic crystals, leading to a flexible device exhibit over 70% retention of efficiency after 1000 bending cycles.